Impact of regional white matter lesions on cognitive function in subcortical vascular cognitive impairment. (May 2014) - Ai, Qing; Pu, Yue-Hua; Sy, Christopher; Liu, Li-Ping; Gao, Pei-Yi
<x content-type="archive" xml:space="preserve">Abstract</x> Objectives: Exact characterization and localization of white matter lesions (WMLs) as they relate and contribute to vascular cognitive impairment is highly debated. The purpose of this study was to investigate the impact of WML on cognitive function by using a new anatomy-based classification method. Methods: We detected WML accurately by using a three-dimensional fluid-attenuated inversion recovery (3D FLAIR) imaging technique and subsequently segmented WMLs by using an anatomy-based method. Participants included 56 consecutive patients diagnosed with subcortical vascular cognitive impairment (SubVCI). The volume of WMLs in different anatomic regions was measured. The volume of the hippocampus, the corpus callosum (CC), any lacunar infarcts, total gray matter (GM), and total brain volumes were also calculated. Results: Hippocampal (P = 0·005) as well as temporal WML volumes (P = 0·039) were both independently associated with mini-mental state examination (MMSE) score. Only the parietal WML volume (P = 0·000) was independently associated with Montreal Cognitive Assessment (MoCA) score. Frontal WMLs were independently correlated with executive function. Occipital WMLs were independently associated with visuospatial and recall function. Language impairment was independently correlated with both parietal GM and parietal WML volume. Functions related to orientation were independently associated with parietal WML volume. Discussion: The volume of WMLs in the temporal region as well as in the hippocampus were both independently associated with MMSE score. For the MoCA score, however, only parietal WML volumes were independently correlated. White matter lesions within different anatomic regions were separately correlated with different subdomains of cognitive function.